Experimental and numerical investigation of heat transfer in an array of impingement jets on a concave surface. (25th December 2017) - Yang, B.; Chang, S.; Wu, H.; Zhao, Y.; Leng, M.
Highlights: The effects of different turbulence models on impingement multi-jet computation. The influence of y + ‾ on impingement multi-jet heat transfer characteristic. Heat transfer capacity could be enhanced with H/d = 10, S/d = 6, and θ = 15°. Abstract: In this article, a combined experimental and computational study was conducted to investigate the heat transfer characteristics of sonic impingement jets on the concave surface of the leading edge of a NACA0015 airfoil. Both the local/average Nusselt number ( Nu / Nu ‾ ) distributions and flow pattern in the impingement region were obtained for H/d ranging from 10 to 25, S/d from 20 to 35, and d from 2 to 5 mm, and the jet inclination angle (θ) varied from 0° to 30°. The suitability of eight different turbulence models were investigated and verified. Streamlines and velocity distributions around the stagnation point were also obtained by numerical calculation. Comparison between the numerical work and the experimental results indicated that (1) both Nu and Nu ‾ were enhanced with H/d = 10, S/d = 30, and θ = 15° in the current study. The impinging multi-jet heat transfer capacity could be augmented if the appropriate structure variables are determined, and (2) enlarging the diameters of the jets holes (d) could not significantly improve the heat transfer performance in the anti-icing system of aircraft.